2018
DOI: 10.1152/jn.00878.2017
|View full text |Cite
|
Sign up to set email alerts
|

Handedness results from complementary hemispheric dominance, not global hemispheric dominance: evidence from mechanically coupled bilateral movements

Abstract: Two contrasting views of handedness can be described as 1) complementary dominance, in which each hemisphere is specialized for different aspects of motor control, and 2) global dominance, in which the hemisphere contralateral to the dominant arm is specialized for all aspects of motor control. The present study sought to determine which motor lateralization hypothesis best predicts motor performance during common bilateral task of stabilizing an object (e.g., bread) with one hand while applying forces to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 107 publications
(128 reference statements)
3
28
1
Order By: Relevance
“…Besides left–right differences in segmental reflexes ( Hultborn and Malmsten, 1983 a , b ; Malmsten, 1983 ; and this study), physiological, anatomical and molecular asymmetries in the spinal cord ( Bakalkin et al , 1980 ; Chazov et al , 1981 ; Bakalkin et al , 1986 ; Bakalkin and Kobylyansky, 1989 ; Nathan et al , 1990 ; de Kovel et al , 2017 ; Kononenko et al , 2017 ; Ocklenburg et al , 2017 ; Kononenko et al , 2018 ; Woytowicz et al , 2018 ) along with general lateralization of motor functions ( Sainburg, 2014 ; Sainburg et al , 2016 ; Knebel et al , 2018 ; Stancher et al , 2018 ) have been reported. Three-quarters of cervical spinal cords are asymmetric with larger right side ( Nathan et al , 1990 ).…”
Section: Discussionsupporting
confidence: 61%
“…Besides left–right differences in segmental reflexes ( Hultborn and Malmsten, 1983 a , b ; Malmsten, 1983 ; and this study), physiological, anatomical and molecular asymmetries in the spinal cord ( Bakalkin et al , 1980 ; Chazov et al , 1981 ; Bakalkin et al , 1986 ; Bakalkin and Kobylyansky, 1989 ; Nathan et al , 1990 ; de Kovel et al , 2017 ; Kononenko et al , 2017 ; Ocklenburg et al , 2017 ; Kononenko et al , 2018 ; Woytowicz et al , 2018 ) along with general lateralization of motor functions ( Sainburg, 2014 ; Sainburg et al , 2016 ; Knebel et al , 2018 ; Stancher et al , 2018 ) have been reported. Three-quarters of cervical spinal cords are asymmetric with larger right side ( Nathan et al , 1990 ).…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, there are complementary specializations of each hemisphere for different aspects of the manual control involved in a role-differentiated bimanual manipulation (RDBMthe preferred hand holds the needle in sewing or the lid when unscrewing a jar, etc.) task (Woytowicz, Westlake, Whitall, & Sainburg, 2018). Again, these differences are relative, not absolute.…”
Section: Character Of Sciencementioning
confidence: 88%
“…Instead, the left hand rested or "hovered", seemingly unable to disengage from its stabilization role. Recently, Woytowicz and colleagues (Woytowicz et al 2018) reported that switching preferred roles of the left and right hand during a simulated "bread-cutting" task was in fact non-optimal for motor performance. By examining relevant characteristics of the movement, they demonstrated that the right hand showed straighter reaching trajectories but was poor at stabilizing, whereas the left hand exhibited more stable holding performance, but was poor at reaching.…”
Section: Bimanual Use Emerges From An Interaction Between Task Demands and Lateralized Motor Control Processesmentioning
confidence: 99%